Phase II study of apatinib combined with temozolomide in patients with advanced melanoma after failure of immunotherapy. Issue 3 (20th February 2022) - Zhou, Li; Yang, Yue; Si, Lu; Chi, Zhihong; Sheng, Xinan; Lian, Bin; Wang, Xuan; Tang, Bixia; Mao, Lili; Yan, Xieqiao; Li, Siming; Bai, Xue; et al.
Abstract : Treatment for advanced melanoma after progression on immunotherapy is limited. This phase II trial (NCT03422445) was conducted to evaluate the efficacy and safety of apatinib plus temozolomide in patients with advanced melanoma after failure of immunotherapy. Patients with unresectable stage III or stage IV melanoma after progression on immunotherapy were treated with temozolomide 300 mg on days 1–5 and apatinib 500 mg daily every 28-day cycle until disease progression or intolerable toxicities. Besides immunotherapy, prior chemotherapy, targeted therapy, and clinical trials were allowed. The primary endpoint was progression-free survival. Secondary endpoints were objective response rate, disease control rate, overall survival, and safety. Of 29 patients, 28 (96.6%) had metastatic diseases, and the predominant subtypes were mucosal [12 (41.4%)] and acral melanoma [eight (27.6%)]. Five (17.2%) patients showed BRAF, CKIT, or NRAS mutation. Five achieved confirmed partial response, with an objective response rate of 17.2%. The disease control rate was 82.8%. The median progression-free survival was 5.0 months [95% confidence interval (CI): 4.7–5.3], and the median overall survival was 10.1 months (95% CI: 5.1–15.0). Grade 3–4 treatment-related adverse events included proteinuria [four (13.8%)], thrombocytopenia [two (6.9%)], hypertension [one (3.4%)], and hyperbilirubinemia [one (3.4%)]. No treatment-related death occurred. Apatinib plus temozolomide demonstrated promising efficacy and manageable safety profile in patients with advanced melanoma after progression on immunotherapy.